No distance too far - Snelling, Lauraine (Snelling, Lauraine. Home to Blessing, 2010)
When she is called home unexpectedly to help in a family medical emergency, physician Astrid Bjorklund learns of a deadly measles outbreak on the nearby Indian reservation. She immediately senses the Spirit tugging her to help the Indians and wonders if her "mission field" is not so far away as she had imagined. But if she follows God's call, will love pass her by?